Leishmania major Modulates Chemokine and Chemokine Receptor Expression by Dendritic Cells and Affects Their Migratory Capacity - Steigerwald, Mario (American Society for Microbiology, 2005)
Dendritic cells (DC) both produce and respond to chemokines. We examined the profiles of chemokines and chemokine receptors expressed by DC and their chemotactic response after interaction with Leishmania major. Expression of the chemokine receptors CCR2 and CCR5 by DC and their responsiveness to the respective ligands, CCL2 and CCL3, were downregulated, while the level of CCR7 and the DC response to its ligand CCL21 were enhanced. These parasite-induced alterations were observed with DC from L. major-resistant and -susceptible mice. In contrast, expression of the chemokine CXCL10 was elicited only in DC from L. major-resistant mice.